Design and Think-Aloud Study of an Immersive Interface for Training Health Professionals in Clinical Skills - Negrão, Matheus Dias; Ferreira, Wesley; Bohrer, Betania; Freitas, Carla M. D. S.; Maciel, Anderson; Nedel, Luciana (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2023: Anais do XXV Simpósio de Realidade Virtual e Aumentada, 2023)
Virtual simulation has been used for decades to improve the practice of technical skills by physicians. However, an important aspect of medical education is learning and practicing non-technical skills, which are commonly taught in role-playing sessions. Using VR simulation for such kind of training would optimize supervision time and allow for training in multiple scenarios. In this paper, we introduce a framework and application to support healthcare professionals in learning multi-step procedures and assess students’ and candidates’ readiness. The framework is an immersive system that allows users to perform general healthcare tasks in a natural environment. It does not require constant monitoring by an expert, making it accessible to larger groups of students and candidates with reduced time and personnel resources. The design also considers individual adaptation to virtual reality by providing in-game ergonomics and interaction accuracy settings. The system was tested through a user study with a pediatrician scenario and underwent a preliminary evaluation in a major hospital.